ANALISIA KEBIJAKAN PERMENKES NOMOR 6 TAHUN 2014 LARANGAN MONGUBINGO: PERSPPEKTIF TRADISI MASYARAKAT ADAT DI KABUPATEN GORONTALO - Alhadar, Sofyan; Gobel, Lisda Van; Nggilu, Rukiah; Sahi, Yayan; Ali, Sukirman H (Universitas Bina Taruna Gorontalo, 2022)
This study aims to examine the prohibition of female circumcision involving the World Helth Organization (WHO) and the National Commission on Women. Where the organization gives legitimacy that female circumcision violates Human Rights. The methods used in this study are qualitative and descriptive research methods. For the location of the study was carried out in Gorontalo Regency. The results showed that the implementation of female circumcision in Gorontalo did not conflict with juridical law in terms of the procedure for implementing female circumcision as stated in the regulation of the Minister of Health of the Republic of Indonesia No. 6 of 2014. In addition, the factor that makes female circumcision mandatory for indigenous peoples in Gorontalo Regency, namely the belief that female circumcision ( Mongubingo) can suppress sexual desire, behavior, and sturdiness in maintaining Islamic law. now. Dnature this is the purpose of female circumcision is actually to regulate the order in religious values, customs and norms that apply to societya as well as the practice of beliefs and symbols of greatness of traditions oriented towards the Custom of serendikan syarak, syarak bersendikan kitabullah (ASQ).